Macroeconomic Uncertainty and Cash Holdings of Top 50 Listed Firms in Vietnam Stock Exchange - Dung Ha, Van (Journal of Reviews on Global Economics, 2020)
This study investigates the impact of macroeconomic uncertainty on cash holdings of top 50 listed firms in Vietnam Stock Exchange. The average of natural logarithm of inflation rate, change in exchange rate, deficit to GNP, and external debt to GNP ratio is used for macroeconomic uncertainty while the ratio of cash and cash equivalent to total assets measures firm cash holdings.Using a dataset of 300 observations from top 50 listed firms in both Ho Chi Minh City Stock Exchange and Hanoi stock Exchange from 2013-2018, the paper employs the basic quantitative methods of Pooled Ordinary Least Squared, Fxed effects model, and Random effects model for analysis. The results indicate that higher macroeconomic uncertainty may lead to higher cash holdings of listed firms in Vietnam Stock Exchange. Some other determinants of firm cash holdings can be named as firm size, the ratio of market and booked value of firm, cash flow, net working capital, firm investment, leverage, and firm dividend. One macroeconomic indicator (the growth rate of money supply) is also found to have positive impacts of cash holdings of firms in Vietnam Stock Exchange.